2010
DOI: 10.1007/s00464-010-1426-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-expandable metallic stent placement for malignant obstruction in patients with locally recurrent gastric cancer

Abstract: Endoscopic SEMS placement for obstruction due to recurrent cancer after total or subtotal gastrectomy is feasible and provides effective short-term palliation, independent of the type of surgical procedure or stent (covered vs. uncovered) used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…We were concerned about the safe and successful placement of the stent, because limited data are available on the safety of SEMS placement in postgastrectomy patients [13, 14]. Song et al [13] placed SEMSs in 39 patients with malignant anastomotic obstructions after gastrojejunostomy and reported their results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We were concerned about the safe and successful placement of the stent, because limited data are available on the safety of SEMS placement in postgastrectomy patients [13, 14]. Song et al [13] placed SEMSs in 39 patients with malignant anastomotic obstructions after gastrojejunostomy and reported their results.…”
Section: Discussionmentioning
confidence: 99%
“…However, aspiration pneumonia, stent migration, and reobstruction occurred in 2, 4, and 2 patients, respectively, with a total complication rate of 23.1%. Kim et al [14] also reported the results for 39 postgastrectomy patients who underwent SEMS placement. The technical success rate was 92% and the total complication rate was 44%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, aspiration pneumonia, stent migration, and reobstruction occurred in 2, 4, and 2 patients, respectively, with a total complication rate of 23.1%. Kim and coworkers [14] also reported the results for 39 postgastrectomy patients who underwent SEMS placement. The technical success rate was 92% and the total complication rate was 44%.…”
Section: Complications Associated With Stent Placementmentioning
confidence: 99%
“…Few data are available about the use of SEMS for the nonsurgical palliative treatment for recurrent malignant gastric outlet obstruction [3][4][5][6][7][8][9][10][11] . To our knowledge, few studies focused on endoscopic placement of SEMS in the recurrence of anastomotic strictures [11][12][13][14][15] . In this setting, the clinical outcomes and complications might differ according to the surgical technique because of the different anastomotic angle or different anatomical alterations during surgery.…”
Section: Introductionmentioning
confidence: 99%